Current smoking improves ulcerative colitis patients’ disease behaviour in the northwest of China - Huihong Zhai; Wenyu Huang; Aiqin Liu; Qianqian Li; Qian Hao; Ling Ma; Feng Yang; Shutian Zhang (Gastroenterology Review)
Introduction : The incidence of ulcerative colitis has increased tremendously over the past few decades, and caused much more attention in China. Several studies have revealed that both environmental and genetic factors play crucial roles in the formation and development of this disease. Among the environmental factors, the smoking condition is highly significant. Although current smoking has been associated with a protective effect on both the development and progression of ulcerative colitis (UC), the clinical characteristics of UC patients with current smoking in China is still unclear. Aim : To clarify the relationship between current smoking and the UC in the northwest of China, patients diagnosed with ulcerative colitis in the General Hospital of Ningxia Medical University from 2003.03 to 2012.09 were assessed. Material and methods : Data were collected about clinical features, cigarette smoking conditions, disease location, and therapeutic requirements. A total of 421 patients were included in this study, at diagnosis, 341 (81%) patients were non-smokers, and the current smokers amounted to 80 (19%). Results : As for disease location, there were no differences between the current smokers and non-smokers regarding proctitis and extensive colitis, but the current smokers had less left-sided colitis than non-smokers (p = 0.049). Based on the Modified Mayo score, heavier smokers had lower scores than other smokers and non-smokers. For the therapeutic requirements, current smokers needed fewer corticosteroids than non-smokers (p = 0.048). Conclusions : We found that current smoking is closely associated with a protective factor for UC.